Observational and modeling studies of oceanic responses and feedbacks to typhoons Hato and Mangkhut over the northern shelf of the South China Sea. (February 2021) - Dong, Wenjie; Feng, Yanqing; Chen, Changsheng; Wu, Zhongxiang; Xu, Danya; Li, Siqi; Xu, Qichun; Wang, Lu; Beardsley, Robert C.; Lin, Huichan; Li, Ruixiang; Chen, Junkun; et al.
Highlights: Observations of Typhoons Hato and Mangkhut highlighted energetic convection processes. Including convection/overturning is critical for simulating a storm-produced oceanic mixed layer. Warming makes ocean mixed layer thinner and thus enhances storm-induced air-sea interactions. Abstract: Meteorological and oceanic responses to Typhoons Hato and Mangkhut were captured by storm-monitoring network buoys over the northern shelf of the South China Sea. With similar shelf-traversing trajectories, these two typhoons exhibited distinctly different features in storm-induced oceanic mixing and oceanic heat transfer through the air-sea interface. A well-defined cold wake was detected underneath the storm due to a rapid drop in sea surface temperature during the Hato crossing, but not during the Mangkhut crossing. Impacts of oceanic mixing on forming a storm-produced cold wake were associated with the pre-storm condition of water stratification. In addition to oceanic mixing produced through the diffusion process by shear and buoyancy turbulence productions, the short-time scale of mixing suggested convection/overturning may play a critical role in the rapid cooling at the sea surface. The importance of convection/overturning to mixing depended on the duration of atmospheric cooling above the sea surface-the longer the atmospheric cooling, the more significant effect on mixing. Including the oceanic mixed layer (OML) in the WRF model was capable of reproducing the observed storm-induced variations of wind and air pressure, but not the air and sea surface temperatures. Process-oriented numerical experiments with the OML models supported both observational and modeling findings. To simulate the storm-induced mixing in a coupled atmospheric and oceanic model, we need to improve the physics of vertical mixing with non-hydrostatic convection/overturning. Warming over the shelf is projected to have a more energetic influence on future typhoon intensities and trajectories. Plain Language Summary: The South China Sea (SCS) is a region vulnerable extremely to tropical cyclones (TCs). Typhoons Hato and Mangkhut were the strongest TCs attacking the SCS in 2017 and 2018, respectively. Storm-monitoring network buoys with a layout along the 50-m isobath over the northern shelf of the SCS captured meteorological and oceanic responses to these two typhoons. The observations revealed that these two typhoons exhibited distinctly different features in storm-induced oceanic mixing and heat transfer, even though with similar shelf-traversing paths and intensities. A well-defined cold wake formed beneath the storm due to a rapid drop in the sea surface temperature during the Hato crossing, but not during the Mangkhut crossing. The data synthesis elucidated that impacts of oceanic mixing on forming a storm-produced cold wake were associated with the pre-storm condition of water stratification. In addition to oceanic mixing produced through the diffusion process by the turbulence shear and buoyancy productions, the short-time scale of mixing suggested that convection/overturning may be a primary physical process that rapidly cooled the sea surface. The importance of convection/overturning to mixing depended on the atmospheric cooling duration above the sea surface, more significant as air-cooling lasts longer. To evaluate the essential role of ocean mixing in typhoon simulation, the Weather Research and Forecasting (WRF) model was applied to simulate these two typhoons under conditions with and without an oceanic mixed layer (OML). Results indicated that including the OML in the WRF reproduced observed storm-induced variations of wind and air pressure but not the air and sea surface temperatures. Process-oriented numerical experiments with the OML models supported both observational and modeling findings. To resolve the OML and vertical mixing, a coupled atmospheric and oceanic model must improve the physics of mixing with non-hydrostatic convection/overturning. The influence of warming on typhoon intensity and pathway is projected to be more energetic in the future.